Robert B. Parker's revelation [compact disc, unabridged] - Parker, Robert B., 1932-2010; Knott, Robert, 1954- (Random House Audio, 2017)
Territorial marshals Virgil Cole and Everett Hitch thought things had finally calmed down in Appaloosa when Boston Bill Black's murder charge was dropped. But all that changed when Augustus Nobel Driggs rolled into town. Square-jawed, handsome, and built like a muscled thoroughbred stallion, Augustus intimidates even his guards from inside his prison cell. So when he and a pack of cold-blooded convicts break out of jail, kidnapping a woman in the process, and it's up to any and all territorial lawmen--including Virgil and Everett--to capture the fugitives and rescue her. But nothing is ever quite what it seems with the ever-elusive Augustus: finally free, he's quickly on his own furious hunt for a hidden cache of gold and the men who double-crossed him.